PENGARUH MODEL GENERATIVE LEARNING TERHADAP KEMAMPUAN ANALISIS SISWA PADA MATERI SISTEM SARAF MANUSIA - Sulton Nawawi; Fitri Oviyanti; Ulul Faizah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
Analysis is a basic ability for students to think critically and include one of the high cognitive that were important to mastered students. Where the ability of high-level thinking was one of the goals of education in the 21st century. The purpose of this study was to determine the effect of Generative Learning model on the Ability of Student Analysis on Matter of Human Nervous System in Class XI IPA SMA Muara Lakitan Musi Rawas Regency. This research used Quasi Experiment method of Nonequivalent Control Group Design. The population of this research was the students of class XI IPA with sampling technique used nonprobability of purposive sampling. With the sample of research class XI IPA 1 and XI IPA 2 which amounted to 69 students. Technique of data collection used multiple choice test amounting to 15 question, observation of model execution, field notes and documentation. Based on analysis result of student's analysis ability showed that mastery of analysis ability indicator in experiment class 67,7% higher than control class that was 55,3%. The improvement of analytical ability can be seen from the N-gain value where the experimental class has a gain value of 0,53 with medium category higher than control class that is 0.19 with low category. The results of hypothesis testing using t test obtained tcount = 3.969 and ttable = 1.670 with 95% confidence level ( = 0.05). The data shows that tcount> ttable, then H0 is rejected and Ha accepted. Thus, it can be concluded that the Generative Learning model has an effect on the students' analysis ability in the XI grade of SMA Negeri Muara Lakitan of Musi Rawas Regency.